In vitro antimicrobial efficacy of tobramycin against staphylococcus aureus biofilms in combination with or without DNase I and/or Dispersin B: A preliminary investigation - Waryah, Charlene Babra; Wells, Kelsi; Ulluwishewa, Dulantha; Chen-Tan, Nigel; Gogoi-Tiwari, J.; Ravensdale, Joshua; Costantino, Paul; Gökçen, A.; Vilcinskas, A.; Wiesner, J.; Mukkur, Trilochan (2017)
© Mary Ann Liebert, Inc. 2017.Staphylococcus aureus in biofilms is highly resistant to the treatment with antibiotics, to which the planktonic cells are susceptible. This is likely to be due to the biofilm creating a protective barrier that prevents antibiotics from accessing the live pathogens buried in the biofilm. S. aureus biofilms consist of an extracellular matrix comprising, but not limited to, extracellular bacterial DNA (eDNA) and poly-ß-1, 6-N-acetyl-d-glucosamine (PNAG). Our study revealed that despite inferiority of dispersin B (an enzyme that degrades PNAG) to DNase I that cleaves eDNA, in dispersing the biofilm of S. aureus, both enzymes were equally efficient in enhancing the antibacterial efficiency of tobramycin, a relatively narrow-spectrum antibiotic against infections caused by gram-positive and gram-negative pathogens, including S. aureus, used in this investigation. However, a combination of these two biofilm-degrading enzymes was found to be significantly less effective in enhancing the antimicrobial efficacy of tobramycin than the individual application of the enzymes. These findings indicate that combinations of different biofilm-degrading enzymes may compromise the antimicrobial efficacy of antibiotics and need to be carefully assessed in vitro before being used for treating medical devices or in pharmaceutical formulations for use in the treatment of chronic ear or respiratory infections.